Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.celrep.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

PAX7 Targets, CD54, Integrin α9β1, and SDC2, Allow Isolation of Human ESC/iPSC-Derived Myogenic Progenitors

Abstract: Pluripotent stem (PS) cell-derived cell types hold promise for treating degenerative diseases. However, PS cell differentiation is intrinsically heterogeneous therefore clinical translation requires development of practical methods for isolating progenitors from unwanted and potentially teratogenic cells. Muscle-regenerating progenitors can be derived through transient PAX7 expression. To better understand the biology, and to discover potential markers for these cells, here we investigate PAX7 genomic targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 54 publications
2
94
1
Order By: Relevance
“…It is also important to note that, although previous reports (Borchin et al, 2013; Magli et al, 2017) have identified other useful and important markers (such as ACHR, NCAM, CD54, and SDC2) for purification of myogenic progenitors, different culture condition and duration, gene overexpression, and cytokine use might be responsible for identification of different markers in these studies. In addition, side-by-side in vitro and in vivo comparison with ERBB3/NGFR markers demonstrated advantage of CD10/CD24 in the current differentiation protocol.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is also important to note that, although previous reports (Borchin et al, 2013; Magli et al, 2017) have identified other useful and important markers (such as ACHR, NCAM, CD54, and SDC2) for purification of myogenic progenitors, different culture condition and duration, gene overexpression, and cytokine use might be responsible for identification of different markers in these studies. In addition, side-by-side in vitro and in vivo comparison with ERBB3/NGFR markers demonstrated advantage of CD10/CD24 in the current differentiation protocol.…”
Section: Discussionmentioning
confidence: 95%
“…During the past decade, several efforts have been made to differentiate PSCs toward skeletal myogenic lineage (Barberi et al, 2007; Borchin et al, 2013; Chal et al, 2015; Choi et al, 2016; Darabi et al, 2008, 2011, 2012; Kim et al, 2017; Magli et al, 2017; Shelton et al, 2014; Tanaka et al, 2013; Tedesco et al, 2012; Xi et al, 2017; Xu et al, 2013). Initial reports by collaborators using myogenic gene overexpression during differentiation provided proof of the concept, i.e., myogenic potential of murine and human PSCs (Darabi et al, 2008, 2011, 2012; Darabi and Perlingeiro, 2016; Tanaka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to their murine counterparts, PAX7-induced PS cell-derived human myogenic progenitors give rise to differentiated myotubes in vitro, and contribute to muscle regeneration in vivo, as shown by myofiber and stem cell engraftment, and improvement of muscle physiological parameters [94, 118]. Further studies aimed at dissecting the molecular function of PAX7 in differentiating human ES cells identified a subset of transcripts undergoing gradual up-regulation during myogenic commitment, as well as the putative PAX7 binding sites that may be responsible for the PAX7-dependent regulation of these genes [118]. Notably, this work enabled the identification of a group of cell-adhesion molecules (CD54 or ICAM1, SYNDECAN2 and INTEGRIN α9β1), which identify the human PAX7-derived myogenic progenitors.…”
Section: Myogenic Induction By Controlled Expression Of Transcriptmentioning
confidence: 99%
“…Notably, this work enabled the identification of a group of cell-adhesion molecules (CD54 or ICAM1, SYNDECAN2 and INTEGRIN α9β1), which identify the human PAX7-derived myogenic progenitors. These findings have important therapeutic implications since surface marker-based isolation techniques are compliant with Current Good Manufacturing Practice (CGMP) procedures [118]. Since PAX7-derived myogenic progenitors can be easily expanded for multiple passages in vitro, adaptation of the purification strategy and culture conditions to CGMP standards may enable the therapeutic translation of this cell population for the treatment of muscle diseases.…”
Section: Myogenic Induction By Controlled Expression Of Transcriptmentioning
confidence: 99%
See 1 more Smart Citation